2017
DOI: 10.1038/jhg.2017.36
|View full text |Cite
|
Sign up to set email alerts
|

Successful newborn screening for Gaucher disease using fluorometric assay in China

Abstract: Gaucher disease (GD) is an inherited metabolic disorder that involves accumulation of glycolipid glucocerebroside in monocyte–macrophage cells, which can result in multiple organ damage. Enzyme replacement and substrate reduction therapies have improved the potential for early diagnosis and treatment. Determining the true incidence of this rare disease is critical for relevant policy establishment. Newborn screening allows for early diagnosis and an comparatively accurate incidence of GD. A fluorometric method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…Further, Polo et al reported a significant elevation of lyso-Gb1 in neonatal dried blood spots using a newly developed and validated assay [ 120 ]. These findings support the value of measuring lyso-Gb1 in dried blood spots as a means to conduct high-throughput newborn screening, first conducted by Kang et al in China [ 3 ]. Although few countries have newborn screening programs that include GD, high rates of false positives have been reported on the measurement of enzyme activity on dried blood spots [ 121 , 122 ], and second-tier analyses are being introduced.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Further, Polo et al reported a significant elevation of lyso-Gb1 in neonatal dried blood spots using a newly developed and validated assay [ 120 ]. These findings support the value of measuring lyso-Gb1 in dried blood spots as a means to conduct high-throughput newborn screening, first conducted by Kang et al in China [ 3 ]. Although few countries have newborn screening programs that include GD, high rates of false positives have been reported on the measurement of enzyme activity on dried blood spots [ 121 , 122 ], and second-tier analyses are being introduced.…”
Section: Discussionsupporting
confidence: 85%
“…Using the NICE STA method, risk of bias in the sole randomized controlled trial was deemed low, although bias regarding the allocation concealment process and between-group baseline similarities was unclear ( Table S1 ) [ 36 ]. Thirty non-randomized clinical trials and observational studies with full-study reporting were assessed using the Newcastle–Ottawa scoring tool [ 3 , 26 , 33 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ], of which 19 were deemed to have a high risk of bias (score 0–3; Table S2 ). Thirty-two animal studies were assessed using the SYRCLE risk of bias tool [ 45 , 53 , 58 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations